2018
DOI: 10.1370/afm.2179
|View full text |Cite
|
Sign up to set email alerts
|

Use of Asthma APGAR Tools in Primary Care Practices: A Cluster-Randomized Controlled Trial

Abstract: PURPOSE The purpose of this study was to assess patient and practice outcomes after introducing the Asthma APGAR (Activities, Persistent, triGGers, Asthma medications, Response to therapy) tools into primary care practices. METHODSWe used a pragmatic cluster-randomized controlled design in 18 US family medicine and pediatric practices to compare outcomes in patients with persistent asthma aged 5 to 45 years after introduction of the Asthma APGAR tools vs usual care. Patient outcomes included asthma control, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Increased adherence to the 2007 US asthma guidelines was linked to "in-control" asthma and higher quality-of-life scores. 21 The implementation of guidelines has led to improved health care outcomes for breastfeeding, 22 -24 safe sleep, 25 -27 diabetic ketoacidosis, 28 acute myocardial infarction, 29,30 and colorectal cancer. 31,32 Systematic literature review of heart failure studies in which researchers directly link process outcomes to clinical outcomes show that many lack statistical power.…”
Section: Figurementioning
confidence: 99%
“…Increased adherence to the 2007 US asthma guidelines was linked to "in-control" asthma and higher quality-of-life scores. 21 The implementation of guidelines has led to improved health care outcomes for breastfeeding, 22 -24 safe sleep, 25 -27 diabetic ketoacidosis, 28 acute myocardial infarction, 29,30 and colorectal cancer. 31,32 Systematic literature review of heart failure studies in which researchers directly link process outcomes to clinical outcomes show that many lack statistical power.…”
Section: Figurementioning
confidence: 99%
“…The acronym “APGAR” stands for “Activities, Persistent, triGGers, Asthma medications, Response to therapy,” it consists in a sequence of questions regarding not only the number of asthma attacks, the presence of diurnal or nocturnal symptoms or the limitation of normal activities due to asthma symptoms, but also the triggers of attacks, the way and the frequency with which the patients take their medicine and whether they think their medicines work or not. Its main distinctive feature is that it gathers a wider spectrum of information than other questionnaires: it mainly focuses on some peculiar aspects of the disease, which are not investigated by means of other questionnaires, but which can be pivotal for tailoring therapy ( 36 ). APGAR's questionnaire is also linked to a care algorithm, which is thought to help the physician to undertake a therapy, while all of the other questionnaires so far adopted only give the physician a simple score.…”
Section: Assessment Of Asthma Controlmentioning
confidence: 99%
“…Prior studies have demonstrated that use of remote monitoring, self-management training, telemedicine, smartphones, and CDSS tools, individually, can improve outcomes. [40][41][42] To our knowledge, however, this is the first intervention to combine these components into a single technological package that effectively integrates with real-world medical practice and the live EMR.…”
Section: Discussionmentioning
confidence: 99%